Réponses

2014-03-29T12:06:52+01:00
52) 1) A=(3x+7)(5x+4)
             = 15x²+12x+35x+28
               = 15x²+14x+28

2)  tu remplaces x par une valeur,  par exemple x=0  et x=2

53)1)  B=(5x-3)(4x+9)
         =20x²+45x-12x-27
           = 20x²+33x-27
 2)  tu prends x= -1 et  x=1


54)1) C=(8-4x)(6x-5)
         = 48x-40-24x²-(-20x)
         = 48x-40-24x²+20x
           = 68x-40-24x²
           = -24x²+68x-40

2)  x= -3    et x= 4
2014-03-29T12:26:57+01:00
(3x+7) (5x+4)
3x * 5x + 3x * 4 + 7 * 5x + 7 * 4
15x +12x +35x+ 28
62x + 28



Ps: * = fois
      x = x